Heavy metals in the air: analysis using Instrument, air pollution and human health - a review - Muhammad Amin, Siti Noor Syuhada; Azid, Azman; Abdullah Sani, Muhamad Shirwan; Ku Yusof, Ku Mohd Kalkausar; Samsudin, Mohd Saiful; Abd Rani, Nurul Latiffah; Khalit, Saiful Iskandar (Penerbit UTM Press, 2018)
Air pollution can harm human health, cause-effect to the environment and trigger factor to property damage. Various researches have proven the connection between air quality and human health. The previous research on epidemiology and laboratory studies demonstrated that ambient air pollutants (for example PM, O3, SO2 and NO2) contribute to various respiratory problems including bronchitis, emphysema and asthma. This present mini-review is to discuss the relationship between human health and air quality. This conceptual paper is focusing on the findings from air quality based on literature review and the significant health effects which related to it. Besides, the principle of analytical instrumentation is also being discussed in order to identify the best instrument in laboratory analysis.